2020
DOI: 10.21203/rs.2.19240/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Are normoglycaemic individuals at risk of depression? The depression-dysglycaemic phenotype from a European population-based cross-sectional study

Abstract: Background Depression is a chronic non communicable disease. It is a growing public health concern with established links with a number of co-morbidities, including diabetes mellitus. The study aimed to estimate the prevalence of depression at a population level, establish the depression sub-population phenotypic characteristics while exploring for links between depression and a spectrum of glycemic abnormalities. Methods A nationally representative cross-sectional study was conducted in Malta between 2014 an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Although recall bias cannot be excluded, the fact that the participants noted the presence of such medical problems merits attention. Indeed, a pre-COVID-19 national study conducted among Maltese adults has already reported a substantial prevalence for both diseases (hypertension 30.12%; depression 17.15%) [19,20]. Hence, disruptions of healthcare services along with self-isolation measures are expected to have aggravated such problems.…”
Section: Discussionmentioning
confidence: 99%
“…Although recall bias cannot be excluded, the fact that the participants noted the presence of such medical problems merits attention. Indeed, a pre-COVID-19 national study conducted among Maltese adults has already reported a substantial prevalence for both diseases (hypertension 30.12%; depression 17.15%) [19,20]. Hence, disruptions of healthcare services along with self-isolation measures are expected to have aggravated such problems.…”
Section: Discussionmentioning
confidence: 99%